A systematic review of factors influencing student interest in online homework - Chen, Liu; Wong, Su Luan; How, Shwu Pyng (Springer, 2023)
Online homework has been emerging with the popularity of online learning. The significance of online homework has been recognised, especially during the outbreak of COVID-19. Although it is regarded as one homework format, studies explicitly targeted at online homework are limited till now, particularly in student interest. As interest is defined as the driver of student learning, it is important to explore the factors influencing student interest in online homework to promote this technology use. Thus, a systematic review of the literature was conducted to identify studies on student interest in online homework with the guide of PRISMA. Based on 23 selected studies, this study unveiled the included studies characteristics and the informed factors influencing student interest in the online homework system or the homework assigned or completed online. The findings of this study showed that background variables, adult guidance and monitoring, and the role of students in the process impact student interest in online homework. As online homework is delivered via technology, other factors, such as content design, the ability of technology use and homework submission methods, are also associated with student interest in online homework. Relevant educational implications are elaborated. Further studies and limitations are also included in this study.